Ecological urban planning and design: A systematic literature review - Heymans, A.; Breadsell, Jessica; Morrison, Greg; Byrne, Joshua; Eon, C. (2019)
Urbanization is a defining feature of the modern age, yet the current model of urban development profoundly alters the natural environment, often reducing biodiversity and ultimately threatening human wellbeing. An ecologically based urban planning and design paradigm should consider a more harmonious relationship. Through a systematic literature review of 57 papers, this research identified relevant concepts and theories that could underpin this new paradigm. It revealed a noticeable increase in academic interest in this subject since 2013 and the development of concepts and theories that reflect a more holistic socio-ecological systems approach to urban planning and design based on a transdisciplinary integration and synthesis of research. Seven main themes underpin the academic literature: ecosystem services, socio-ecological systems, resilience, biodiversity, landscape, green infrastructure, as well as integrated and holistic approaches. Six of these can be organised into either a sustainability stream or a spatial stream, representing the foundations of a potential new ecological urban planning and design paradigm that applies sustainability-related concepts in a spatial setting. The final theme, integrated and holistic, includes concepts that reflect the fundamental characteristics of this new paradigm, which can be termed 'urban consonance'.